Advances of Wnt signalling pathway in dental development and potential clinical application. (2nd October 2019) - Lu, Xi; Yang, Jun; Zhao, Shouliang; Liu, Shangfeng
ABSTRACT: Wnt signalling pathway is widely studied in many processes of biological development, like embryogenesis, tissue homeostasis and wound repair. It is universally known that Wnt signalling pathway plays an important role in tooth development. Here, we summarized the function of Wnt signalling pathway during tooth initiation, crown morphogenesis, root formation, and discussed the therapeutic potential of Wnt modulators.